Applying the Healthcare Failure Mode and Effect Analysis (HFMEA) Method for the Risk Management of Self-Developed Electronic Medical Records (EMRs) in Hospitals - Luqman Hakiem; Iwan Dewanto; Sriyanto Sriyanto; Babucarr Jassey (Universitas Muhammadiyah Yogyakarta, 2022)
The organization of electronic medical records (EMR) in hospitals is vital. In cases where EMRs are developed independently, failures that hamper the hospital's operations could sometimes occur. Risk management is needed to identify, reduce, and eliminate potential failures. This study aimed to analyze a risk management by using the Healthcare Failure Mode and Effects Analysis (HFMEA) method to reduce the risk of failure in the outpatient EMR development process at Baitul Hikmah General Hospital (RSBH). This observational research applied an action research design and was conducted using the HFMEA method. It analyzed the outpatient EMR development process at RSBH. Research data was obtained through a mixed method where information was collected from focus group discussions (FGD) and calculated risk priority numbers (RPN). The research subjects were determined by the purposive sampling technique (HFMEA team). The HFMEA form was used as the research instrument. At least 33 failure modes were identified. These failure modes were evenly distributed throughout the outpatient EMR development process at RSBH. The top five failure modes received treatment actions and their outcomes were measured. Four out of the five failure modes showed a significant decrease in RPN value. In short, risk management analysis using the FMEA method could significantly reduce the potential for failure in the outpatient EMR development process at RSBH